Cost-effectiveness analysis design for interventions to prevent children's oral disease - Spetz, Joanne; Rose, Johnie; Kahn, James G.; Lin, Tracy; Levy, Douglas; Pugach, Oksana; Hyde, Susan; Borrelli, Belinda; Henshaw, Michelle; Martin, Molly; Nelson, Suchitra; Ramos-Gomez, Francisco; et al. (Frontiers in Oral Health, 2024)
Introduction: In 2015, the National Institute of Dental and Craniofacial Research (NIDCR) launched the Multidisciplinary Collaborative Research Consortium to Reduce Oral Health Disparities in Children, supporting four randomized trials testing strategies to improve preventive care. A Coordinating Center provides scientific expertise, data acquisition and quality assurance services, safety monitoring, and final analysis-ready datasets. This paper describes the trials’ economic analysis strategies, placing these strategies within the broader context of contemporary economic analysis methods. Methods: The Coordinating Center established a Cost Collaborative Working Group to share information from the four trials about the components of their economic analyses. Study teams indicated data sources for their economic analysis using a set of structured tables. The Group meets regularly to share progress, discuss challenges, and coordinate analytic approaches. Results: All four trials will calculate incremental cost-effectiveness ratios; two will also conduct cost-utility analyses using proxy diseases to estimate health state utilities. Each trial will consider at least two perspectives. Key process measures include dental services provided to child participants. The non-preference-weighted Early Childhood Oral Health Impact Scale (ECOHIS) will measure oral health-related quality of life. All trials are measuring training, implementation, personnel and supervision, service, supplies, and equipment costs. Conclusions: Consistent with best practices, all four trials have integrated economic analysis during their planning stages. This effort is critical since poor quality or absence of essential data can limit retrospective analysis. Integrating economic analysis into oral health preventive intervention research can provide guidance to clinicians and practices, payers, and policymakers.